Domestic Stalking, Violation of Protective Orders, and Homicide in Chicago: The Influence of Social Disorganization and Gender Inequality - Sacra, Sarah (2018)
Domestic violence has been considered a serious issue for many decades. This problem manifests itself physically, sexually, and emotionally and can affect anyone. However, most of the domestic violence literature focuses specifically on physical intimate partner violence. Various theoretical frameworks have been utilized to explain the occurrence of domestic violence including social disorganization theory and gender inequality. These explanations are limited, however, with the former primarily extended to physical assault and the latter focusing on violence against women. This study is important as it extends our knowledge of how these two perspectives can be applied to domestic violence through the analysis of domestic stalking, violation of protective orders, and homicide at a structural level. Incident data for these crimes that occurred in 2016 were obtained from the Chicago data portal and demographic data were obtained from the 2016 American Community Survey's 5-year estimates. Univariate, multivariate, and spatial analyses were conducted at the census tract level to determine the associations between the two theoretical frameworks and each crime. Statistical results indicate that social disorganization theory and gender inequality can partially explain the occurrence of domestic stalking, violation of protective orders, and homicide. Concentrated disadvantage was one of the most consistent predictors of domestic violence, but the direction of the relationship varied across models. There were significant gender inequality factors, but the directions also varied. Spatial results demonstrate clustering of the crimes in areas characterized by increased social disorganization as well as areas possessive of certain indicators of gender inequality. This study is unique as it employed both social disorganization and gender inequality frameworks at a structural level, employed various spatial analysis and mapping techniques, and it analyzed understudied acts of domestic violence to set precedent and open doors for future inquiry